The impact of DMARD and anti-TNF therapy on functional characterization of short-term T-cell activation in patients with rheumatoid arthritis - A follow-up study - Szalay Balázs (PLOS ONE, 2014)
Rheumatoid arthritis (RA) is a chronic autoimmune disease characterized by a systemic dysfunction of T-cells. In this study we tested the impact of DMARD and anti-TNF agents on short-term activation characteristics of T-cells. We enrolled 12 patients with newly diagnosed RA (naïve RA) who were treated with methothrexate (MTX) and glucocorticsteroid (GCS) and 22 patients with established RA non responding to conventional DMARD therapy who were treated with different anti-TNF agents. Nine healthy volunteers served as controls. Blood samples were taken at baseline, then at 4th and 8th week of therapy. The characteristics of several intracellular activation processes during short-term activation of T-cells including cytoplasmic Ca2+ level, mitochondrial Ca2+ level, reactive oxygen species (ROS) and nitric oxide (NO) generation were determined by a novel flow-cytometry technique. At baseline, the tested processes were comparable to controls in naïve RA. During GCS therapy, cytoplasmic Ca2+ level and ROS generation decreased. After the addition of MTX to GCS cytoplasmic Ca2+ level became comparable to controls, while ROS generation decreased further. In DMARD non responders, cytoplasmic Ca2+ level was higher than controls at baseline. The cytoplasmic Ca2+ level became comparable to controls and ROS generation decreased during each of the three anti-TNF-α agent therapies. Mitochondrial Ca2+ level and NO generation were unaltered in all of the patient groups. These results indicate that intracellular machinery is affected in T-cells of RA patients. This may alter the behavior of T-cells during activation. Different therapeutic approaches may modulate the abnormal T-cell functions. © 2014 Szalay et al.